Employing Songs to Improve the Students’ Mastery of Simple Past Tense - Hartiwi, Juni; Sutiwi, Sri (LinguaScopes: International Journal of Language Education, 2024)
The purpose of this study is to find out if songs can help students become more proficient in the simple past tense. Twenty-five ninth-grade students from SMPN 20 Bandar Lampung are the focus of this study. According to the study's findings, pupils' proficiency with the simple past tense considerably increases following treatment. This indicates that songs can be used as an effective learning tool for learning simple past tense.